2019
DOI: 10.1530/erc-19-0240
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of primary bilateral macronodular adrenal hyperplasia

Abstract: Primary bilateral macronodular adrenal hyperplasia (PBMAH) is a highly heterogeneous entity. The incidental identification of an increasing number of cases has shifted its clinical expression from the rarely encountered severe forms, regarding both cortisol excess and adrenal enlargement, to mild forms of asymptomatic or oligosymptomatic cases with less impressive imaging phenotypes. Activation of cAMP/PKA pathway, either due to alterations of the different downstream signaling pathways or through aberrantly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 86 publications
0
40
0
Order By: Relevance
“…Bilateral adrenal masses, along with cortisol secretion and the documentation of familial cases, suggests a genetic predisposition. Recently, Armadillo repeat containing 5 (ARMC5) mutations have been described in familial cases and in sporadic patients with CS [152,153]. Although ARMC5 mutations reduce the steroid secretory capacity of each cell, the overall cortisol secretion is increased due to massive enlargement of the adrenals [154][155][156].…”
Section: Question 6: Is a Different Management Required For Bilateral Adrenal Incidentaloma?mentioning
confidence: 99%
“…Bilateral adrenal masses, along with cortisol secretion and the documentation of familial cases, suggests a genetic predisposition. Recently, Armadillo repeat containing 5 (ARMC5) mutations have been described in familial cases and in sporadic patients with CS [152,153]. Although ARMC5 mutations reduce the steroid secretory capacity of each cell, the overall cortisol secretion is increased due to massive enlargement of the adrenals [154][155][156].…”
Section: Question 6: Is a Different Management Required For Bilateral Adrenal Incidentaloma?mentioning
confidence: 99%
“…However, the procedure also leads to increased surgical mortality compared with unilateral adrenalectomy, and one fifth of patients after bilateral adrenalectomy suffer from Nelson's syndrome or adrenal crisis (Reincke et al 2015;Nagendra et al 2019). In contrast, unilateral adrenalectomy has been reported to lead to remission in more than 90% of BMAH patients with a minimal risk for adrenal insufficiency (Vassiliadi and Tsagarakis 2019). Moreover, recently, a prospective cohort has reported the effectiveness of simultaneous removal of total and partial adrenal glands, so-called adrenal-sparing surgery, with no perioperative complications (Tanno et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the utility of CT volumetry remains to be investigated, particularly in BMAH cases harboring pathologically different lesions. Previous reports have shown that BMAH could be concomitant with aldosterone-producing adenomas, pheochromocytomas and also metastasis of non-adrenal origin (Tokumoto et al 2017;Hayakawa et al 2011;Vassiliadi and Tsagarakis 2019). Besides, BMAH is genetically heterogenous and the severity of hypercortisolemia could depend on the genetic causes (Espiard et al 2015;Vassiliadi and Tsagarakis 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ACTH-independent CS can mainly be attributed to cortisol-producing adrenal adenomas. Adrenocortical carcinomas, uni-/bilateral adrenal hyperplasia, and primary pigmented nodular adrenocortical disease (PPNAD) may account for some of these cases as well ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%